CC-001 An unusual cause of dyspepsia. (23rd September 2015) - Aryal, K R; Higham, A; Crighton, I; Ball, C
Abstract : Introduction: Dyspepsia is common presentation in gastrointestinal disease. We report a case of new onset dyspepsia referred for open access gastroscopy who was found to have an unusual cause of the pain. Methods: Case is reported with investigation results and his subsequent management. Results: A 63-year-old man was referred for open access gastroscopy for new onset dyspepsia. Gastroscopy under throat spray showed a gall stone in the stomach and what appeared to be a fistulous opening adjacent to the pylorus. Further enquiry, immediately after endoscopy revealed a history of upper abdominal pain 5 years ago following which an abdominal ultrasound detected gall stones. Apart from a raised γ-glutamyl transferase (yGT) of 326 IU/l and slightly raised bilirubin of 20 IU/l, all other liver function tests were normal. An abdominal ultrasound showed gas in the biliary tree; the gall bladder could not be visualised properly and the common bile duct measured 8 mm. A computerised tomography (CT) scan subsequently showed a gall bladder which was adherent to the pylorus with a partially calcified calculus in the gall bladder and gas in the cystic duct and intrahepatic ducts. At operation through a right subcostal incision, the pyloric antrum was densely adherent to the gall bladder and there was a cholecystogastric fistula. Small stones were present in the gall bladder but there were no stones in the stomach. The fistula was taken down and the gastric wall was closed with 2/0 polydioxanone suture. A per-operative cholangiogram showed free flow of contrast to duodenum with no stone on the common bile duct. Cholecystectomy was completed; the post operative period remained uneventful and he was discharged home on the fifth post operative day. Histology of the gall bladder revealed chronic cholecystitis with food debris in the gall bladder in keeping with a diagnosis of cholecystogastric fistula. The fistulation between gall bladder and stomach is very rare and <50 cases of cholecystogastric fistula have been reported in the English literature since 1925. The cholecystogastric fistula is more common in women beyond the sixth decade of life. These cases mostly present with mild dyspepsia, but cases presenting with gastric outlet obstruction and upper gastrointestinal haemorrhage have also been described. The diagnosis is made by gastroscopy, ultrasound or CT scan. Conclusion: Cholecystogastric fistula is a rare cause of dyspepsia. Removal of the gall bladder with closure of the gastric wall has a good outcome if the patient is fit for operation.